Notas para a compreensão da constituição do sujeito em Freud - Gelamo, Rodrigo Pelloso [UNESP] (My University, 2010)
In this paper we intend to understand the functioning of Freudian psychism concerning the constitution of the psychic subject in his relation with knowledge. In order to do that, we will analyze one of the most important writings by Freud: An Outline of Psycho-Analysis. This choice was made because we think that the author synthesizes his thought in that book, whose maturity makes possible for us to access a later elaboration of the functioning and the conceptions we intend to analyze: The regions of Psychic apparatus; The problem of the Psycho-Analysis approach: science and philosophy; and The psychic qualities of the subject.

Neste trabalho temos a intenção de compreender o funcionamento do psiquismo freudiano no que diz respeito à constituição do sujeito psíquico. Para isso, vamos analisar um dos mais importantes escritos de Freud: Esboço de Psicanálise. Essa escolha se dá pelo fato de entendermos que o autor sintetiza seu pensamento nessa obra, cuja maturidade nos possibilita ter acesso a uma elaboração mais tardia dos funcionamentos e conceituações que pretendemos analisar, a saber: As regiões do aparelho psíquico, O problema da abordagem psicanalítica: ciência e filosofia; e As qualidades psíquicas do sujeito.
Notes for understanding the constitution of the subject in Freud
Keywords: Filosofia contemporânea; Subjetividade; sujeito